Discovering new antimicrobial agents - Chebotaryova, Ksenia; Konon, Anastasia; Nesterenko, Natalia (My University, 2011)
This paper is devoted to the problems of finding new effective antimicrobials. The study of the antimicrobial properties of surfactants have been carried out at the Biotechnology and Ecology faculty NUFT. Surfactant is a substance composed of two functional parts: a polar basic hydrophilic group and a non-polar one with a hydrophobic residue. Due to this molecular structure solutions of surfactants can reduce surface and interfacial tension. The purpose of this study is to investigate the antimicrobial properties of surfactants Rhodococcus erythropolis EK-1 and Acinetobacter calcoaceticus K-4. Strains R. erythropolis EK-1, and A. calcoaceticus K-4.
Keywords: поверхнево-активні речовини; антимікробна дія; сурфактант; кафедра біотехнології і мікробіології; кафедра іноземних мов професійного спрямування